The Ghrelin Receptor (Ghsr) Gene Polymorphism in Indonesian Local Chicken and Crossbreed Is Associated With Carcass Traits - Khaerunnisa, Isyana; Jakaria, Jakaria; Arief, Irma Isnafia; Budiman, Cahyo; Sumantri, Cece (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
Ghrelin receptor (GHSR) gene is candidate gene for growth performance in chicken by modulating growth hormone release from the pituitary by binding to its ligand of ghrelin. Ghrelin gene, or growth hormone secretagogue (GHS) gene, is well known as feed intake and energy homeostasis regulator in mammals and birds. The objectives of this study were to identify the polymorphism of the T1857C GHSR locus in Indonesian local chicken and to evaluate its effects on carcass traits. The gene polymorphism was identified using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using Hin6I restriction enzyme. Effect of genotype on carcass composition was analyzed using SAS General Linear Model (GLM) procedure. The genotyping was performed on 343 individuals including Merawang, Pelung,Â Sentul, Kampung, broiler (strain Cobb, parent stock), F1 crossbred of Kampung x broiler (strain Cobb, parent stock), and F2 crossbred of Kampung x broiler (strain Cobb, parent stock). All individuals were successfully amplified and were resulted in a 470 bp PCR product. This locus was polymorphic with two alleles (T and C) and three genotypes (TT, CT, and CC). The T allele and TT genotype were predominant in all populations. Individuals with CT genotype were significantly had higher live weight at 26w, carcass weight, commercial cuts weights, and muscles weights than TT genotype in F2 crossbred of Kampung x broiler population. Association of the T1857C GHSR locus-polymorphism with chicken carcass composition has been described in Indonesian chicken, providing evidence that GHSR might be an important candidate gene for chicken carcass traits.